The wMel Strain of Wolbachia Reduces Transmission of Chikungunya Virus in Aedes aegypti (2016)
ABSTRACT: Background: New approaches to preventing chikungunya virus (CHIKV) are needed because current methods are limited to controlling mosquito populations, and they have not prevented the invasion of this virus into new locales, nor have they been sufficient to control the virus upon arrival. A promising candidate for arbovirus control and prevention relies on the introduction of the intracellular bacterium Wolbachia into Aedes aegypti mosquitoes. This primarily has been proposed as a tool to control dengue virus (DENV) transmission; however, evidence suggests Wolbachia infections confer protection for Ae. aegypti against CHIKV. Although this approach holds much promise for limiting virus transmission, at present our understanding of the ability of CHIKV to infect, disseminate, and be transmitted by wMel-infected Ae. aegypti currently being used at Wolbachia release sites is limited. Methodology/Principal Findings: Using Ae. aegypti infected with the wMel strain of Wolbachia that are being released in Medellin, Colombia, we report that these mosquitoes have reduced vector competence for CHIKV, even with extremely high viral titers in the bloodmeal. In addition, we examined the dynamics of CHIKV infection over the course of four to seven days post feeding. Wolbachia-infected mosquitoes remained non-infective over the duration of seven days, i.e., no infectious virus was detected in the saliva when exposed to bloodmeals of moderate viremia, but CHIKV-exposed, wild type mosquitoes did have viral loads in the saliva consistent with what has been reported elsewhere. Finally, the presence of wMel infection had no impact on the lifespan of mosquitoes as compared to wild type mosquitoes following CHIKV infection. Conclusions/Significance: These results could have an impact on vector control strategies in areas where Ae. aegypti are transmitting both DENV and CHIKV; i.e., they argue for further exploration, both in the laboratory and the field, on the feasibility of expanding this technology beyond DENV.